DIFFUSIVELY ALLOYED COMPOUNDS MADE OF METAL DISCARD WITH A REDUCED MELTING TEMPERATURE FOR OBTAINING WEAR RESISTANT COATINGS USING INDUCTION HARD-FACING TECHNOLOGIES - V. G. Shcherbakou (Литьë и металлургия)
The technology of obtaining diffusion doped alloys made from metal scrap is reviewed in the article. The influence of short term preprocessing at high temperature on structure formation by concentrated energy sources within the further induction deposit is reviewed. A mechanism of a contact eutectic melting in diffusion doped alloys at short term high temperature treatment is described and suggested in this work. It was shown that such kind of processing of diffusion doped alloys is a perspective way of treatment when using induction hard-facing technologies for obtaining wear resistant coatings. A resource and energy saving technology was developed for obtaining wear resistant coatings based on diffusion doped alloys from metal scrap treated using induction hard-facing process.